PERAN DEI DALAM MENINGKATKAN KINERJA ORGANISASI: ANALISIS LITERATUR PADA PERSPEKTIF MANAJEMEN SDM - Latif, Latif; Wibowo, Cokorda Agung (Yayasan Education and Social Center, 2025)
Diversity, equity and inclusion (DEI) in human resource management (HRM) is increasingly becoming a major concern in modern organizational strategies. This study aims to explore the role of DEI in improving organizational performance through a literature review approach of recent research published between 2020 and 2025. The results show that effective implementation of DEI has a positive impact on innovation, creativity, productivity, and employee well-being. In addition, inclusive leadership acts as a key catalyst to ensure that DEI values are optimally integrated into organizational policies and culture. However, while the benefits of DEI are widely recognized, its implementation still faces challenges such as resistance to change, systemic bias in hiring and promotion processes, and a lack of measurable strategies to assess the effectiveness of DEI programs. This study also identifies best practices that organizations can adopt, including the development of fairer hiring policies, ongoing anti-bias training, and the use of technology and data analytics to monitor the success of DEI initiatives. The management implications of the findings confirm that the success of DEI depends not only on policies, but also on committed leadership and the involvement of all stakeholders in creating an inclusive work environment. While the findings of this study provide valuable insights, there are some limitations to note, such as the lack of longitudinal research that can measure the long-term impact of DEI on organizational performance, as well as the variability of DEI implementation across different industries and cultural contexts. Therefore, future research is recommended to adopt a more empirical and contextual approach to better understand the dynamics of DEI and to develop more adaptive and effective implementation models for organizations in different industries.